Tube Well Use as Protection Against Rotavirus Infection During the Monsoons in an Urban Setting. (28th November 2019) - Martinez, Pamela P; Mahmud, Ayesha S; Yunus, Mohammad; Faruque, A S G; Ahmed, Tahmeed; Pascual, Mercedes; Buckee, Caroline O
Abstract: Rotavirus, a diarrheal pathogen spread via fecal-oral transmission, is typically characterized by a winter incidence peak in most countries. Unlike for cholera and other waterborne infections, the role of sanitation and socioeconomic factors on the spatial variation of rotavirus seasonality remains unclear. In the current study, we analyzed their association with rotavirus seasonality, specifically the odds of monsoon cases, across 46 locations from 2001 to 2012 in Dhaka. Drinking water from tube wells, compared to other sources, has a clear protective effect against cases during the monsoon, when flooding and water contamination are more likely. This finding supports a significant environmental component of transmission. Abstract : We examined the association of sanitation and socioeconomic factors with rotavirus seasonality and found that drinking water from tube wells, which are less likely to be contaminated, has a protective effect against rotavirus during the monsoon season in Dhaka, Bangladesh.